Uncovering Factors Contributing to Poor Asthma Control among Asthmatic Patients in Erbil City - Kurdistan Region - Khoshnaw, Zahir S. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Asthma is a heterogeneous disease, usually characterized by chronic airway inflammation and variable expiratory airflow limitation.Objective: The objective of this study was to uncover factors contributing to poor asthma control in Erbil City, Iraq.Methods: To assess asthma control in Erbil City a cross-sectional observational study was conducted on 200 patients with asthma from the 1st, of June to the 31st, of December 2023.  Demographics, clinical characteristics, triggers, comorbidities, inhaler problems, causes of visit, and state of asthma control were evaluated using Global Initiative for Asthma 2023 as the assessment tool questionnaire. Asthma control was divided into three levels: controlled, partly controlled, and uncontrolled.Results: In this study, 200 patients with asthma (108 females and 92 males) were studied. The mean age ± SD of the patients was 35.61 ± 17.182 years and the female-to-male ratio was nearly 1:1. Asthma control was very poor as only 24 patients (12%) were controlled. Neither sex nor age group has a statistically significant association with asthma control. Factors significantly associated with asthma control included improper inhaler technique (45.5%), fear of addiction (29%) improper inhaler prescription (27.5%), coat (23%), device type (22.5%), infections (21%), indoor and outdoor exposure (18%), tobacco smoking (17%), allergic rhinitis (28.5%), gastroesophageal reflux disease (21.5%) and short-acting beta agonist alone therapy 104(52%). Other factors were non-significantly associated with asthma control such as emotional stress (9.5%), food allergy (8.5%), obesity (15%), atopic dermatitis (6%), obstructive sleep apnea (15%), and pregnancy (5.5%).Conclusion: The current study concluded that factors associated with uncontrolled asthma were improper inhaler technique, fear of addiction, improper inhaler prescription, cost, device type, infections, indoor and outdoor exposure, tobacco smoking, allergic rhinitis, Gastro-esophageal Reflux Disease and short-acting beta agonist alone therapy.